(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2020)
The present article makes a brief study on the legal regime of the right to recognition of authorship and the figure of the ghost writer in Brazilian law. In order to do so, it makes use of the judicial decisions rendered in the Bruna Surfistinha case, which discussed the authorship of the literary work “O doce veneno do escorpião” (The sweet poison of the scorpion), which reports on the life of the character Bruna Surfistinha. It is a research that uses descriptive methodology, based fundamentally on bibliographic research, which is done to analyze the judicial solution given to the case object of the study. The most relevant issues of the matter are analyzed, such as the right to recognition of authorship, the work protected by the copyright law, as well as the conventions involving the figure of the ghost writer. It is also worth mentioning the presentation of brief notes on the problem of the ghost writer in Germany and France. Therefore, the objective of this work is to discuss if the judicial solution given to the Bruna Surfistinha case was the most adequate, considering the copyright, the right to the recognition of authorship and the ghost writer conventions.